Potential Applicability of Impact Echo Method on Pavement Base Materials as a Nondestructive Testing Technique. Issue 1 (January 2017) - Mahedi, Masrur; Hossain, Sahadat; Faysal, Mohammad; Khan, Mohammad Sadik
The use of both recycled asphalt pavement and recycled concrete aggregates is increasing considerably in pavement construction. These materials are relatively weak and have to be stabilized with cement or other stabilizers. However, because of product variability and lack of strength and stiffness, their applicability has to be evaluated extensively. Traditionally practiced methods of evaluation might be unreasonable in terms of time, cost, reliability, and applicability. Rapid nondestructive methods, such as the spectral analysis of surface wave, impact echo, pulse velocity, and so forth, have the potential to be inexpensive and less time-consuming, as well as offering low variability of the test results. The objective of the study was to assess the potential applicability of the impact echo method in evaluating recycled pavement base materials. Six combinations (0%–100%, 10%–90%, 30%–70%, 50%–50%, 70%–30%, and 100%–0%) of recycled asphalt pavement and recycled concrete aggregates, respectively, treated by four amounts of portland cement (0%, 2%, 4%, and 6%), were evaluated by impact echo, unconfined compression, and repeated-load triaxial test. From the test results, the range of P-wave velocity was between 5, 500 in./s and 18, 000 in./s, the compressive strength varied from 10 pounds per square inch (psi) and 415 psi, and the tangent modulus range was from 2.8 kips per square inch (ksi) to 41 ksi. Statistical models based on P-wave velocity data were derived for predicting elastic modulus, compressive strength, and resilient modulus. It was found that impact echo has significant potential in characterizing the strength and stiffness properties of cement-treated recycled base materials, which confirms the effectiveness of recycled materials in pavement applications.